Hospitalization costs among immobile patients with hemorrhagic or ischemic stroke in China: a multicenter cross-sectional study - Liu, Hongpeng (BMC Health Serv Res, 2020)
BACKGROUND: In this study, we aimed to analyze the hospitalization costs for immobile patients with hemorrhagic stroke (IHS) or ischemic stroke (IIS) in China and to determine the factors associated with hospitalization costs. METHODS: We evaluated patients with IHS and IIS hospitalized between November 2015 and July 2016 in six provinces or municipality cities of China. Linear regression analysis was used to examine the association with hospitalization costs and predictors. RESULTS: In total, 1573 patients with IHS and 3143 with IIS were enrolled and analyzed. For IHS and IIS, the average length of stay (LoS) was 17.40 ± 12.3 and 14.47 ± 11.55 days. The duration of immobility was 12.11 ± 9.98 and 7.36 ± 9.77 days, respectively. Median hospitalization costs were RMB 47000.68 (interquartile range 19,827.37, 91,877.09) for IHS and RMB 16578.44 (IQR 7020.13, 36,357.65) for IIS. In both IHS and IIS groups, medicine fees accounted for more than one-third of hospitalization costs. Materials fees and medical service fees accounted for the second and third largest proportions of hospital charges in both groups. Linear regression analysis showed that LoS, hospital level, and previous surgery were key determinants of hospitalization costs in all immobile patients with stroke. Subgroup analysis indicated that hospital level was highly correlated with hospitalization costs for IHS whereas pneumonia and deep vein thrombosis were key factors associated with hospitalization costs for IIS. CONCLUSIONS: We found that hospitalization costs were notably higher in IHS than IIS, and medicine fees accounted for the largest proportion of hospitalization costs in both patient groups, perhaps because most patients ended up with complications such as pneumonia thereby requiring more medications. LoS and hospital level may greatly affect hospitalization costs. Increasing the reimbursement ratio of medical insurance for patients with IHS is recommended. Decreasing medicine fees and LoS, preventing complications, and improving treatment capability may help to reduce the economic burden of stroke in China.